International criminal law and the African girl child soldier: does the international criminal law framework provide adequate protection to the African girl child soldier? - Hlatshwayo, Belinda S T (Department of Public Law, 2017)
This dissertation aims to answer the question: does the international criminal law framework provide adequate protection to the African girl child soldier? The motivation for the choice of this question came about in my final year of LLB. I conducted research on crimes against humanity committed by Boko Haram, and found a lot of research had been conducted on the use of children in war. I became particularly interested in the use of girl child soldiers because of the disparity between them and their male counterparts - how they were used during conflicts and the definitions of child soldier in international statutes. The constant reference in international treaties of child soldiers as those who take part in 'direct hostilities', I felt excluded girl child soldiers from protection as girl child soldiers are often used as base-camp soldiers, spies and often times sexually, physically and emotionally abused.